Removal of a mixture of formaldehyde and methanol vapors in biotrickling filters under mesophilic and thermophilic conditions: Potential application in ethanol production. (3rd June 2022) - Al-Faliti, Mitham; Dvorak, Bruce; Aly Hassan, Ashraf
ABSTRACT: Ethanol is a significant source of energy as a biofuel; however, its production using corn involves the generation of harmful emissions from both fermentation tanks and dryers. Scrubbers control the emissions from fermentation tanks, while the emissions from the dryers are controlled by regenerative thermal oxidizers. Potential alternatives to these energy- and water-intensive technologies are biotrickling filters (BTFs). In this study, two BTFs were operated in parallel to treat formaldehyde and methanol emissions in a volumetric ratio of 4:1, one at 25°C (mesophilic), and the other at 60°C (thermophilic). The mesophilic BTF simulated emissions from fermentation tanks, while the thermophilic BTF simulated emissions from dryers. Both beds were operated at an empty bed residence time of ~30 s and influent formaldehyde concentrations of 20, 50, and 100 parts per million per volume (ppmv). Formaldehyde polymerization was reduced in this study by adding NaOH to pH levels of 7.0–7.4 and heating the solution to a temperature of 60°C. BTFs have successfully removed formaldehyde at typical ethanol plants emissions ~21 ppmv . The BTF technology have the potential in replacing the conventional air treatment methods used at ethanol plants. Implications : Currently, ethanol plants remove and treat hazardous air pollutants (HAPs) using wet scrubbers from the fermenter off-gasses and using thermal oxidizers to combust off-gasses. The utilization of biotrickling filters (BTFs) for HAP removal generally and formaldehyde particularly has wide implication in the field of renewable energy. Utilizing BTFs in the 200+ ethanol plants in USA will save cost and reduce water and energy needs significantly. BTFs can reduce an ethanol plant's carbon intensity (CI) by 1 to 3 g CO2 /MJ. This can result in roughly $50 million per year in additional revenue in Nebraska for instance.